Children with a history of prematurity presenting with snoring and sleep‐disordered breathing: A cross‐sectional study. (18th April 2013) - Manuel, Anura; Witmans, Manisha; El‐Hakim, Hamdy
Abstract : Objectives/Hypothesis: To report on the prevalence of premature (PM) birth in a consecutive series of children treated for snoring and sleep‐disordered breathing (S/SDB), the parameters specific to their management and variables predictive of disease severity. Study Design: A retrospective study was undertaken at a tertiary pediatric hospital. Methods: Children with history of PM and presenting with S/SDB were identified from a prospectively kept surgical database. We set out to determine the prevalence of PM among the patients presenting with S/SDB who required airway evaluations and surgery. Pulse oximetry is overnight recordable oxygen saturation and heart rate tracing that provides information about hypoxemia during sleep. This was performed on all children preoperatively. The pulse oximetry findings were used to plan for perioperative monitoring and care. A multivariable analysis was used to identify factors predictive of abnormal pulse oximetry studies. We evaluated the associated diagnoses, surgical procedures required, and response to treatment in these selected children. Results: Fifty‐seven out of 1, 038 patients were PM (33 males; mean age, 62.09±34.91 months; range, 4–190 months). The mean gestational age was 30.3±4.0 weeks. The prevalence rate of PM among patients treated surgically for SDB is 5.5% (95% CI 5.2–5.8) at our center. Comorbid pulmonary and gastrointestinal disorders were encountered on 23 (40%) and 17 (29.8%) occasions, respectively, and were the most commonly encountered comorbid diagnostic categories. Large airway abnormalities were encountered in 11 (19.3%) children, and the most common were subglottic stenosis (four) and laryngeal paralysis (four). Comorbid respiratory disease was negatively predictive of abnormal pulse oximetry (coefficient −0.35, P <.05). Postoperative respiratory outcomes correlated with abnormal pulse oximetry (coefficient 0.3; P <.05). Conclusions: Our findings suggest children with PM presenting to pediatric otolaryngology require a comprehensive evaluation for S/SDB. A significant proportion of children with S/SDB and a history of PM frequently had pulmonary and gastrointestinal comorbidities in our cohort. One‐half required admission postoperatively, and these were predictable based on preoperative pulse oximetry. Respiratory comorbidity was negatively predictive of severity of SDB. Inversely, children with untreated pulmonary comorbidities are more likely to have postoperative complications. Level of Evidence: 2b. Laryngoscope, 123:2030–2034, 2013